2023
DOI: 10.1038/s41598-023-29894-1
|View full text |Cite
|
Sign up to set email alerts
|

The tight junction protein occludin modulates blood–brain barrier integrity and neurological function after ischemic stroke in mice

Abstract: Blood–brain barrier (BBB) disruption contributes to brain injury and neurological impairment. Tight junctions (TJs) and cell–cell adhesion complexes develop between endothelial cells in the brain to establish and maintain the BBB. Occludin, the first transmembrane protein identified in TJs, has received intense research interest because numerous in vitro studies have suggested its importance in maintaining BBB integrity. However, its role in maintaining BBB integrity after ischemic stroke is less clear owing t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Tight junctions between brain endothelial cells are crucial for maintaining the integrity and selective permeability of the neurovasculature. [43][44][45] Therefore, we next evaluated whether differences in levels of junctional proteins were associated with the increased cortical extravasation of IgG and fibrinogen in APOE3 Cre+/− mice. At the mRNA level, we did not find any differences between APOE3 Cre−/− and APOE3 Cre+/− mice for tight junction (Ocln and Cldn5) and adherens junction (Cdh5, Ctnnb1, and Ctnnd1) transcripts (Figure 2C; Figure S4).…”
Section: Endothelial Knockdown Of Apoe3 Is Sufficient To Cause Neurov...mentioning
confidence: 99%
“…Tight junctions between brain endothelial cells are crucial for maintaining the integrity and selective permeability of the neurovasculature. [43][44][45] Therefore, we next evaluated whether differences in levels of junctional proteins were associated with the increased cortical extravasation of IgG and fibrinogen in APOE3 Cre+/− mice. At the mRNA level, we did not find any differences between APOE3 Cre−/− and APOE3 Cre+/− mice for tight junction (Ocln and Cldn5) and adherens junction (Cdh5, Ctnnb1, and Ctnnd1) transcripts (Figure 2C; Figure S4).…”
Section: Endothelial Knockdown Of Apoe3 Is Sufficient To Cause Neurov...mentioning
confidence: 99%
“…The transmembrane part consists of occludin [11,12], junctional adhesion molecules (JAM) [13] and representatives of the claudin family, while the cytoplasmatic plaque is built of proteins with the PDZ domain-ZO-1, ZO-2 and other proteins, e.g., cingulin [10].…”
Section: Tight Junctionsmentioning
confidence: 99%
“…Previous studies have shown that the downregulation of occludin can significantly reduce transcutaneous/transendothelial resistance (TEER) and increase paracellular diffusion ( 70 ). Compared to wild-type mice, the permeability of the BBB significantly increases in occludin-deficient mice after stroke ( 71 ). Many factors, such as matrix metalloproteinase-9 (MMP-9), ubiquitination, phosphorylation, tumor necrosis factor, IL-1β, and IFN-γ, participate in regulating the expression of occludin ( 69 ).…”
Section: Structural Physiological and Pathological Roles Of The Bbbmentioning
confidence: 99%